Science, Environment, Technology And Society (SETS) to Improve Cognitive Science Learning Outcomes for Elementary School Students - Mangkuwibawa, Hilman; Carliyan, Yayan; Azhar, Sofia Fauziah (Al-Aulad: Journal of Islamic Primary Education, 2024)
This research aims to determine the difference in the average increase in students' cognitive learning outcomes in science subjects using the Science, Environment, Technology and Society (SETS) approach and the conventional approach. This research uses a quasi-experimental design with a non-equivalent control group design. The population of this research is all fifth grade students from one of the elementary schools in Bandung Regency for the 2023/2024 academic year. The research population was 22 experimental class students and 24 control class students. Data collection through descriptive tests in the form of pretest and posttest. The test instrument in this research was developed by applying expert judgment. Data analyzed using the t test shows that the t value = 9.003 and the sig value. (2-tailed) = 0.000 < 0.05 then ????0 is rejected. This means that there is a difference in the average increase in cognitive learning outcomes for class V students in science subjects using the SETS approach and the conventional approach. The average N-Gain value of the control class is 0.079 with medium criteria. Meanwhile, the experimental class is 0.530 with medium criteria. So it can be concluded that this research uses cognitive learning outcomes. The Science, Environment, Technology, Society (SETS) approach is an alternative for Natural Sciences (IPA) subjects that makes it easier for students to develop learning outcomes.